1998
DOI: 10.1097/00043764-199802000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Leukemia in Children Living Near High-Voltage Transmission Lines

Abstract: We conducted a study to examine the risk of leukemia between 1987 and 1992 among children living near high-voltage transmission lines (HVTL) in three urban districts of northern Taiwan. Twenty-eight cases of leukemia among some 120,696 children aged 14 years or less were reported to the national cancer registry between 1987 and 1992. Compared with children living in households more than 100 meters away from HVTL, children living in households less than 100 meters from HVTL experienced an essentially elevated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Epidemiological studies suggest a connection between ELF-EMF exposure and certain diseases. Such exposure may play a role in the development of childhood leukaemia [Li et al, 1998] or in the progress of Alzheimer's disease [Harmanci et al, 2003]. ELF-EMF exposure may stimulate the secretion of b-amyloid peptide in exposed cultured neuroglioma cells [Del Giudice et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies suggest a connection between ELF-EMF exposure and certain diseases. Such exposure may play a role in the development of childhood leukaemia [Li et al, 1998] or in the progress of Alzheimer's disease [Harmanci et al, 2003]. ELF-EMF exposure may stimulate the secretion of b-amyloid peptide in exposed cultured neuroglioma cells [Del Giudice et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we may compare the present results to those from studies using distance from homes to a HVPL 6,7,[15][16][17][18] or magnetic fields calculated based on the distance. [4][5][6][7]19 Of these, two studies showed a clear association with reasonable statistical confidence.…”
Section: Case Ascertainmentmentioning
confidence: 95%
“…In Sweden, Feychting and Ahlbom 6 reported an increased risk of childhood leukemia associated with living within 50 m of HVPLs (odds ratio: 2.9; 95% CI: 1.0-7.3). In Taiwan, Li et al 18 found an increased risk of leukemia among children who resided within 100 m of HVPLs (standardized incidence ratio: 2.43; 95% CI: 0.98-5.01). The risk estimate Applying small area analysis, we found an increased risk of childhood hematological malignancies among children who lived in districts near HVPLs.…”
Section: Case Ascertainmentmentioning
confidence: 99%
“…Most suggested increased risk associated to higher exposure, although, in general, 95% Confidence Intervals had null risk in� cluded 41,53,54,55,56,57 .…”
Section: Childhood Leukemiamentioning
confidence: 99%